P63 UPLC/MS/MS assay for the simultaneous determination of seven antibiotics in human serum – application to pediatric studies. Issue 6 (17th May 2019) - Magreault, S; Chaussenery-Lorentz, O; Storme, T; Jacqz-Aigrain, E
Abstract : Background: Antimicrobials are widely used in children but pediatric dose regimens are not always validated, and PK studies, required to validate dosage, are difficult to conduct in children. Low sampling volume limits the number of PK samples drawn per patient and analytical methods adapted to small volumes are not always available. Due to the wide inter-patient pharmacokinetic (PK) variability in children, particularly neonates, therapeutic drug monitoring is required to adapt dosage to individual patients. In such clinical and analytical context, our aim was to develop a unique, rapid and highly sensitive ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) assay to quantify 7 antibiotics (amoxicillin, azithromycin, cefotaxime, ciprofloxacin, meropenem, metronidazole and piperacillin) in low sample volumes (50 µL) for both routine monitoring and pharmacokinetic studies. Methods: After protein precipitation by acetonitrile, the antibiotics and their associated deuterated internal standard were separated on a Waters Acquity UPLC HSS T3 (100 mm x 2.1 mm; 1.8 µm). The mobile phases consisted of a gradient of ammonium acetate (pH 2.4; 5mM) and acetonitrile acidified with 0.1% (v/v) formic acid (started ratio of 93:7, v/v), run at 0.5 mL/min flow rate (total run time: 2.75 min). Ions were detected in the turbo-ion-spray-positive and multiple-reaction-monitoring modes. Results: This method was linear from 0.1–50 µg/mL. Accuracy and precision were evaluated using Quality Control (2, 10, 35 µg/mL). Validation of the method proved that precision, selectivity and stability were all within the recommended limits. Conclusion: This method has the advantage of a unique, efficient and standardized analytical tool for rapid measurement of 7 antibiotics in low blood volume. It has been successfully applied for routine activity and pharmacokinetic studies in children and neonates. Disclosure(s): Nothing to disclose.